Pengembangan Media Interaktif Berbasis Nearpod Untuk Meningkatkan Motivasi dan Hasil Belajar Materi Sholat Berjama'ah - Siti Norhidayah; Jasiah (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2025)
This study aims to design and develop an interactive learning media based on Nearpod, focusing on enhancing conceptual understanding, motivation, student engagement, and the internalization of congregational prayer (Salat Berjamaah) values in Fiqh lessons for seventh-grade students at MTs. The background of this study is based on low student motivation and active participation, as well as suboptimal understanding of the meaning of worship, due to teacher-centered learning, which affects students’ cognitive and affective outcomes. The research employed a Research and Development (R&D) approach using the ADDIE model, which includes analysis, design, development, implementation, and evaluation stages. The research subjects consisted of 20 seventh-grade students at MTs An-Nur Palangka Raya. The instruments used included validation sheets from subject-matter and media experts, student response questionnaires, and learning outcome tests in the form of pretests and posttests. The results indicated that the Nearpod learning media developed was highly feasible, with validation scores of 82% from media experts and 92% from subject-matter experts, yielding an overall feasibility score of 87%. Student responses reached 90%, categorized as very practical. Pedagogically, the use of Nearpod media proved to increase motivation, active engagement, and students’ conceptual understanding. From an Islamic education perspective, this media contributes to instilling discipline, togetherness, and spiritual responsibility in the practice of congregational prayer.